CATALASE AND GLUTATHIONE PEROXIDASE ENZYME LEVELS IN THE SERUM OF DIABETIC RATS GIVEN A DECOCTION OF JAVANESE GINSENG (TALINUM PANICULATUM) LEAF SIMPLICIA - Angel Marinda; I Nyoman Suarsana; I Nyoman Suartha; I Gusti Ayu Agung Suartini; Anak Agung Sagung Kendran; I Made Kardena (Buletin Veteriner Udayana, 2026)
Diabetes mellitus is a chronic metabolic disease characterized by hyperglycemia and increased oxidative stress caused by excessive Reactive Oxygen Species (ROS). Oxidative stress may affect endogenous antioxidant enzymes, including catalase (CAT) and glutathione peroxidase (GPx). This study aimed to analyze the effect of Java ginseng leaf simplicia decoction (Talinum paniculatum) on serum CAT and GPx levels in diabetic rats. Twenty male Sprague-Dawley rats were divided into four groups: normal control (P0), diabetic control (P1), diabetic rats treated with Java ginseng leaf decoction 50 g/100 mL (P2), and diabetic rats treated with 100 g/100 mL (P3). Diabetes was induced using a single intraperitoneal injection of streptozotocin at 40 mg/kg body weight, and treatment was administered orally for 21 days. Serum CAT and GPx levels were measured using ELISA and analyzed using ANOVA followed by Duncan’s test. The results showed that CAT levels were significantly different among groups (P<0.05), while GPx levels were not significantly different (P>0.05). The 100 g/100 mL treatment group showed CAT levels closer to the normal group. It can be concluded that Java ginseng leaf simplicia decoction has potential antioxidant effects in diabetic rats by improving oxidative stress conditions. Further studies are recommended using more specific extraction methods and additional oxidative stress biomarkers.